PETA KOMPETENSI PROFESI OPERATOR MESIN PRODUKSI DAN GAP KOMPETENSI ANTARA KOMPETENSI LULUSAN SMK JURUSAN TEKNIK PEMESINAN DENGAN TUNTUTAN DUNIA KERJA (Studi kasus pada Bengkel Pemesinan di Kota Surakarta) - Herman Saputro; Bambang Pr. Bambang Pr.; C. Sudibyo C. Sudibyo (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2013)
This research purpose is to explore extensively about the competencies required in the workplace, especially in profession of machine operators. The research also aims to find the gap that exists between the competence of vocational school graduates majoring in machinery with the demands of competence in the workplace. The research method used in this study is exploratory qualitative research method. From this research it can be seen that the macro level profession competence of machine operators can be classified into 3 groups of competencies, that is: 1) base competency, 2) Core Competency, and 3) supporting competency. Based on the base competency map, there was a gap between vocational school graduates with professional competence of machine operators, that is 1) competency to read engineering drawings and 2) competency using hand tools. Based on core competency map, 33% of vocational school graduates on levels less capable to work in core area of the machine operator profesion. Based on supporting-competency map, workshop-leaders and senior machine operators have assessed the ability of vocational school graduates are also less capable to perform the service to consumers.